Odysseus at Shabbat Dinner: Hospitality Ethics in Genesis and The Odyssey - Kurtz, Yoni (Iggrot Ha'Ari, 2022)
The Hebrew Bible and Homer’s Greek epics differ significantly in their attention to detail, among other significant literary aspects, but their uniquely massive size relative to other ancient works lends them particularly well to analysis. This investigation can yield deeper understandings of their moral stances. Within ancient Greek literature, hospitality stands alone as an unquestioned moral imperative, while the Hebrew Bible is filled with prescriptions for moral living. With this in mind, hospitality provides a valuable perspective for comparison between these two cultures. Genesis and The Odyssey each heavily feature hospitality, so comparing these two monumental works allows us to flesh out how differing hospitality expectations reflect each society’s ethical emphases. My findings contradict and challenge the misconception that Greek hospitality is not concerned with a guest’s identity, and shows how the hospitality ethics in Genesis and The Odyssey diverge with regards to their treatment of guests whose social class is ambiguous.